Solutions journalism, a solution? Filipino journalists' perceptions on the emergence and impact of solutions journalism in the Philippines - Abio, Marian Louise L.
Solutions journalism is a burgeoning form of journalistic writing that adopts a comprehensive and evidence-based approach to explore various responses to societal Issues. Unlike traditional problem-centered reporting, solutions journalism focuses on uncovering and analyzing the solutions implemented by individuals or communities, delving into the challenges, successes, limitations, and recommendations associated with them. This approach not only informs readers but also encourages them to actively engage with their communities and contribute to addressing societal problems. Although solutions journalism is not yet widely practiced by journalists in the Philippines, recent years have witnessed the emergence of groups such as Solutions Journalism Philippines, highlighting a growing interest in the concept. Furthermore, some Filipino journalists are actively involved with the Solutions Journalism Network, a global institution dedicated to promoting the approach worldwide. This study aims to examine the perceptions of Filipino journalists regarding the emergence and impact of solutions journalism in the local context. Through qualitative, semi-structured interviews with Filipino solutions journalists, the study explores their insights, experiences, and perspectives on solutions journalism, drawing upon the hierarchy of influences and Entman's types of frames as theoretical frameworks.